2003
DOI: 10.1001/archopht.121.10.1364
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Clinical Course of Dry Eye Syndrome

Abstract: To assess subjective symptoms, tear function factors, and ocular surface morphology in the clinical course of patients with dry eye syndrome under treatment within an observation period of up to 8 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 21 publications
(14 reference statements)
3
46
0
2
Order By: Relevance
“…Researchers have reported that subjects with SS have decreased meibum expressibility and quality [38], as well as increased meibomian gland dropout [39, 40] and dysfunction [38, 40, 41]. Further, SS patients have a reduced volume [1, 42], stability [39], lipid layer [39], and surface activity [43] of tears, heightened tear film evaporation [44, 45], ocular surface damage [1, 42], and increased DED symptoms [1, 41]. In effect, as indicated by Akpek et al [46], SS patients have combined aqueous and evaporative DED.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported that subjects with SS have decreased meibum expressibility and quality [38], as well as increased meibomian gland dropout [39, 40] and dysfunction [38, 40, 41]. Further, SS patients have a reduced volume [1, 42], stability [39], lipid layer [39], and surface activity [43] of tears, heightened tear film evaporation [44, 45], ocular surface damage [1, 42], and increased DED symptoms [1, 41]. In effect, as indicated by Akpek et al [46], SS patients have combined aqueous and evaporative DED.…”
Section: Discussionmentioning
confidence: 99%
“…17 In brief, tear film BUT was measured by touching the inferotemporal bulbar conjunctiva with a fluorescein sodium strip, wetted with a preservative-free isotonic sodium chloride solution. The mean value of a total of three measurements was recorded.…”
Section: Patients' Datamentioning
confidence: 99%
“…15 The IC score was designed for observing the course of dry eye patients over a long period, and for the statistical evaluation of morphological changes. 16,17 The aim of this study was to evaluate the IC score on impression cytological specimens of 398 patients with dry eye syndrome as a diagnostic tool in relation to the type and severity of disease. The IC scores and the score points for each morphological parameter (IC subscores) of patients with simple dry eye (S-DE), patients with Sjö gren's syndrome and dry eye (SS-DE), and patients with dry eye and connective tissue disease (CTD-DE) were calculated and compared.…”
Section: Introductionmentioning
confidence: 99%
“…DES is even a symptom of many systemic diseases. In particular, people affected by Sjögren syndrome often experience DES as a common complication [16,17]. Diagnostic tests comprising a grading of the disease are generally clinical [18,19].…”
mentioning
confidence: 99%